KETEPATAN FONETIS DAN GANGGUAN WICARA PADA ANAK PRASEKOLAH DI PAUD ARJUNA - Kholik Kholik (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2023)
This study aims to describe how the phonological accuracy of preschoolers at Arjuna Early Childhood Education. This research is a descriptive research. The data source used is preschool children at Arjuna Paud. Data collection techniques use recording, observing, and note-taking techniques. The data analysis technique used is descriptive analysis technique by means of analyzing. Describe and conclude which phonemes experience inaccuracies and phonemes that experience phoneme deletion or change.The results of this study indicate that the phonological inaccuracies that occur when children speak or speak are in the alveolar apico phoneme sounds /r/, and bilabial sounds /b/, /m/, /w/ and /p/, /s/ , /t/, /d/. in the child's language there is also deletion and phoneme changes such as the word /ballon/ disappears into /alon/, while the phoneme changes occur in the word /jambu/ to /hambu/. The impact of this phonological inaccuracy resulted in a change in the meaning of the word according to the KBBI dictionary. As in o word /panda/ becomes /anda/, the word panda means an animal that resembles a bear with a distinctive black color on the eyes, ears, arms and legs. Meanwhile, your word means a greeting for the person you are talking to.